Population-dependent effects of ocean acidification - Bethanie Carney Almroth; Susanne P. Eriksson; Helen Nilsson Sköld; Kristina Sundell; Hannah L. Wood (Proceedings of the Royal Society B: Biological Sciences, 2016)
Elevated carbon dioxide levels and the resultant ocean acidification (OA) are changing the abiotic conditions of the oceans at a greater rate than ever before and placing pressure on marine species. Understanding the response of marine fauna to this change is critical for understanding the effects of OA. Population-level variation in OA tolerance is highly relevant and important in the determination of ecosystem resilience and persistence, but has received little focus to date. In this study, whether OA has the same biological consequences in high-salinity-acclimated population versus a low-salinity-acclimated population of the same species was investigated in the marine isopod Idotea balthica. The populations were found to have physiologically different responses to OA. While survival rate was similar between the two study populations at a future CO 2 level of 1000 ppm, and both populations showed increased oxidative stress, the metabolic rate and osmoregulatory activity differed significantly between the two populations. The results of this study demonstrate that the physiological response to OA of populations from different salinities can vary. Population-level variation and the environment provenance of individuals used in OA experiments should be taken into account for the evaluation and prediction of climate change effects.